154 Enhancing Communication Between Foundation Doctors and Radiologists. (4th May 2021) - Chuang, Y H; Jones, V; Trail, M; Szewczyk-Bieda, M; Nandwani, G M
Abstract: Introduction: Facilitating radiological imaging for patients is an essential task for all Foundation Year (FY) doctors. Achieving competence in this task can expedite patient management. We evaluated the confidence and skills of FYs in facilitating radiological imaging before and after introduction of formal training. Method: Surgical FYs working at a teaching hospital were surveyed to evaluate their baseline level of competence in booking and discussing imaging with radiology colleagues. Parameters were measured on a Likert scale, including confidence in discussing requests and satisfaction of their own performance following discussions. Eight radiology consultants were surveyed to evaluate their opinions on FYs' communication and established areas for improvement. A teaching session was then delivered to improve communication skills. Furthermore, PACCSS poster was introduced to remind the FYs of the salient information required when discussing imaging. Results: One month after the intervention, the participants were re-surveyed. This demonstrated a statistically significant improvement in self-reported confidence from 5.3/10 to 7.3/10 (p < 0.001), and in satisfaction of own performance from 5.4/10 to 7.0/10 (p < 0.001). Conclusions: We identified deficiencies in surgical FY doctors' confidence and skills in facilitating radiological imaging. There was a demonstrable benefit with focused training. Inter-specialty communication should be introduced into under- and post-graduate educational curriculum.